Penerapan Model Pembelajaran Make-A Match (Mencari Pasangan) untuk Meningkatakan Kemampuan Siswa Mata Pelajaran PKn Siswa Kelas IV SDN 1 Terong Tawah - H. Parsas (PALAPA, 2018)
This research is based on the low grade of Civics subject of grade 4 students of SDN 1 Terong Tawah. The problem of this research is how the application of the method of applying Make - A Match learning model to improve students' ability of Civics subject of fourth grade students of SDN 1 Terong Tawah Year 2017. The purpose of this study is to improve the learning outcomes of fourth grade students of SDN 1 Terong Tawah year 2017. This research is a classroom action research. This study consists of two cycles, each cycle consists of four stages namely, planning, implementation, observation and reflection. data collection techniques used in the study are test and observation. Factors studied were student factors and teacher factors. The results of this study indicate that the use of Make-A Match learning method to increase the students 'ability of Civics subjects of fourth grade students of SDN 1 Terong Tawah Year 2017 is marked by the improvement of students' learning mastery in every cycle, that is 42.5% for cycle I 77.5% for cycle II Improvement of student learning outcomes is measured by the completion of student learning completeness in a classical manner in each cycle.